Understanding the Role of Self-Efficacy in Sports Performance: A Longitudinal Study - Dr. Xiaokai Yang; Kaza Mojtahe, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The primary goal of this research project is to evaluate the influence of self-efficacy in athletic performance. This longitudinal study gives primary research data analysis to identify the research study employed useful research questions connected to self-efficacy and sports performance. This question is dependent on whether it is open-ended or closed-ended. The research study employed SPSS software for this aim, and the outcomes were useful. The descriptive statistic analysis, one-way ANOVA test analysis, variance component analysis, chi-square analysis, and the initial main test between dependent and independent variables are all performed. Self-efficacy considers independent, and sports performance is the dependent variable. An athlete's self-efficacy beliefs are greatly influenced by their coaches, teammates, and the broader sports environment. Coaches, trainers, and sports psychologists can improve performance results by creating effective techniques to boost players' self-belief and confidence by better understanding the components that affect self-efficacy. The overall research study found that there are negative links between self-efficacy and sports performance.